2017
DOI: 10.1037/pas0000447
|View full text |Cite
|
Sign up to set email alerts
|

Explaining discrepancies in assessment protocols: Trait relevance and functional equivalence.

Abstract: Inconsistencies among independent sources of information about psychological constructs are widely documented, but not adequately explained. Measurement error as the primary explanation, though historically popular, is no longer tenable. Yet, even as assessors acknowledge that various measures of the same construct are not necessarily interchangeable, there are no agreed upon frameworks to discern the unique contribution of each measure in multiinformant and multimethod assessment protocols. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
1
5
1
Order By: Relevance
“…The findings contribute to knowledge on the longitudinal relationships between executive functions, cyberbullying, and depressive symptoms while providing opportunities for future research to examine other possible mediating and/or moderating mechanisms between these variables (e.g., personality traits and psychological symptoms). Finally, despite the fact that the discrepancy in the results between performance and self-report measures has been discussed in the literature (Teglasi et al, 2017 ), in this study significant relationships were found between measures obtained with different methods (i.e., performance tasks to assess executive functions and self-report questionnaires for the rest of the variables). This provides support to the findings of this study since the performance tasks are less biased by variables such as depressive symptoms, which could lead an adolescent to minimize his or her skills in the use of executive functions.…”
Section: Discussioncontrasting
confidence: 64%
“…The findings contribute to knowledge on the longitudinal relationships between executive functions, cyberbullying, and depressive symptoms while providing opportunities for future research to examine other possible mediating and/or moderating mechanisms between these variables (e.g., personality traits and psychological symptoms). Finally, despite the fact that the discrepancy in the results between performance and self-report measures has been discussed in the literature (Teglasi et al, 2017 ), in this study significant relationships were found between measures obtained with different methods (i.e., performance tasks to assess executive functions and self-report questionnaires for the rest of the variables). This provides support to the findings of this study since the performance tasks are less biased by variables such as depressive symptoms, which could lead an adolescent to minimize his or her skills in the use of executive functions.…”
Section: Discussioncontrasting
confidence: 64%
“…To evaluate the possible differences between raters (parent vs. teacher) of clinical elevations for DG participants, we used chi-square analyses. Collectively, each of our three approaches to analyses are supported by past research (e.g., De Los Reyes & Kazdin, 2004;McConaughy & Ritter, 2002;Stewart et al, 2017;Teglasi et al, 2017), and by using each of them, we can more comprehensively evaluate our second research question.…”
Section: Discussionmentioning
confidence: 80%
“…De Los Reyes and Kazdin ( 2004) pointed out that the mathematical properties of the different measures of informant agreements and disagreements can lead to different conclusions and that these measures are not interchangeable. For this reason, to show a more comprehensive interpretation of the agreements and disagreements of parents' and teachers' ratings of specific impairments in singular or multiple domains of EF across contexts, we used three complementary approaches that have been recommended to assess agreements and disagreements between raters (e.g., McConaughy & Ritter, 2002;Stewart et al, 2017;Teglasi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Disordered perception and thought both influence information processing, but the requirements to assess them may not be equivalent across different measures and contexts. It is therefore important to interpret correlational evidence in light of the causal influences of a phenomenon on assessment responses given under various performance conditions with different measures and life settings (Teglasi, 2013;Teglasi et al, 2017). To generalize from a measure of disordered thinking and perception to real-life functioning, it is necessary to match information processing requirements to respond appropriately in both contexts (Annotti & Teglasi, 2017).…”
Section: Measures and Constructsmentioning
confidence: 99%